TCR Nanoclusters as the Framework for Transmission of Conformational Changes and Cooperativity - Blanco, Raquel; Alarcon, Balbino (Frontiers in Immunology, 2012)
Increasing evidence favors the notion that, before triggering, the T cell antigen receptor (TCR) forms nanometer-scale oligomers that are called nanoclusters. The organization of the TCR in pre-existing oligomers cannot be ignored when analyzing the properties of ligand (pMHC) recognition and signal transduction. As with other membrane receptors, the existence of TCR oligomers points out to cooperativity phenomena. We review the data in support of conformational changes in the TCR as the basic principle to transduce the activation signal to the cytoplasm and the incipient data suggesting cooperativity within nanoclusters.